2021
DOI: 10.1155/2021/2986489
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-2355-5p Promotes the Proliferation of Head and Neck Squamous Cell Carcinoma via Suppressing NISCH Expression

Abstract: Background. MicroRNAs (miRNAs) have emerged as crucial regulators in various cancers. However, the potential role of miR-2355-5p in head and neck squamous cell carcinoma (HNSC) remains unclear. Methods. Bioinformatics methods were implemented to find the candidate target gene of miR-2355-5p. Quantitative real-time PCR was performed to detect RNA expression levels of miR-2355-5p and NISCH, while western blot was carried out for the detection of protein levels of NISCH and cell cycle-related biomarkers. CCK-8, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…It is worth mentioning that expression of NISCH may also be regulated by microRNAs. In HNSC, it was reported that miR-2355-5p decreased NISCH expression, leading to higher tumor cell proliferation [ 77 ], and knockdown of miR-23b and miR-27b was reported to upregulate nischarin and repress breast cancer growth [ 78 ]. However, OncomiR (an online resource that explores the miRNomes across TCGA cancers) [ 79 ] did not show significant correlations of NISCH mRNA with miRNAs in any of the cancers we examined (not shown).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that expression of NISCH may also be regulated by microRNAs. In HNSC, it was reported that miR-2355-5p decreased NISCH expression, leading to higher tumor cell proliferation [ 77 ], and knockdown of miR-23b and miR-27b was reported to upregulate nischarin and repress breast cancer growth [ 78 ]. However, OncomiR (an online resource that explores the miRNomes across TCGA cancers) [ 79 ] did not show significant correlations of NISCH mRNA with miRNAs in any of the cancers we examined (not shown).…”
Section: Discussionmentioning
confidence: 99%